PENGARUH KEPEMIMPINAN PEMBELAJARAN (INSTRUCTIONAL LEADERSHIP) KEPALA SEKOLAH TERHADAP KUALITAS PEMBELAJARAN GURU - Akmaluddin; Panni Ance Lumbantobing; Fitriani Manurung (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the principal's instructional leadership, the quality of teacher teaching, and the influence of the principal's instructional leadership on the quality of teacher teaching at the UPT of Public Elementary School 064998, Medan City. This study uses a quantitative approach with an explanatory method. The sample population and this study were all 30 teachers at the UPT of Public Elementary School 064998, Medan City, so the sampling technique used was total sampling. Data were collected using a questionnaire and analyzed using descriptive and inferential statistics through simple linear regression. The results of the study indicate that the principal's instructional leadership is in the high category, while the quality of teacher teaching is in the good category. The results of the regression analysis indicate that the principal's instructional leadership has a positive and significant influence on the quality of teacher teaching. The principal's instructional leadership contributes 50.0% to the variation in teacher teaching quality, while the rest is influenced by other factors outside this study. The findings of this study confirm that strengthening the role of the principal as a learning leader is an important strategy in improving the quality of teacher teaching in elementary schools.